Implementation of Activity-Based Language Week Program in Improving Arabic Communication Skills at Ma’had al-Jami’ah - Tribhuwan Kumar; Irsal Amin; Mahyudin Ritonga; Sobhan Sobhan (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2022)
Improving Arabic speaking skills for non-native speakers are faced with serious problems, so educational institutions must be able to make new breakthroughs in efforts to improve communication skills. Ma'had al-Jami'ah IAIN Padangsidimpuan determines that a program is seen as part of efforts to improve Arabic communication skills, namely "activity-based language week". This study aimed to describe the implementation of the activity-based language week program at Ma'had Al-Jamiah IAIN Padangsidimpuan in Arabic learning, especially maharah kalam projected as an alternative to reduce the problematic Arabic skills of PTKI students. This study was carried out with a qualitative approach where data were collected through participatory observation, interviews, and document studies. Data were analyzed using the Miles and Huberman technique consisting of collection, reduction, presentation, and drawing conclusions. Based on the results, the activity-based language week program was well implemented in four activities with various activities, namely ilqa' al-mufrodat, muroja'ah, hiwar practice, and muhadhoroh lughoh. These four activities were proven to be able to minimize the difficulties of students in learning Arabic based on improving skills in using Arabic as a means of daily communication. This study recommends further researchers to conduct trials related to the effectiveness of its implementation or examine the language week program.